The charmed library : a novel - Moorman, Jennifer, 1978- (Harper Muse, 2026)
"Like many other public libraries, the one in Blue Sky Valley, North Carolina, is a haven for readers. But it's also unlike any other. In this library, fictional characters step off the page into real life. Assistant librarian Stella Parker has no idea. Still reeling from her father's death and--more recently--a breakup, she hasn't noticed. All she knows is she's stuck in a job she's overqualified for and stumped about what to do with her life. Everything changes when she burns her beloved journal. Words matter to Stella. For as long as she can remember, she's seen them. Words appear--in varying colors and fonts--rising from surfaces, bouncing over objects, and even wiggling out of people. Words give her insight into emotions and untold stories. But the words change for Stella after she burns her journal. Suddenly they're demanding, urgent--and painful. Then Stella stumbles upon strange characters in the library after hours. One is an oddly familiar World War II soldier who introduces himself as Jack--Jack Mathis, the main character from her favorite book. A fictional hero and Stella's first crush. Standing in front of her in the flesh. Jack tells Stella about the magic hidden in the library. Skeptical, Stella rashly invites a villain to visit, and chaos ensues. As she discovers the importance of protecting the library's secret and gets to know the real Jack, words continue to appear. What are they trying to tell her? Much too quickly, Stella is faced with the reality that all stories must end, and magic comes at a price. The characters who visit the library can only stay for fourteen days. And Jack's time is almost up."--Page 4 of cover.